Individual psychological therapy in an acute inpatient setting: Service user and psychologist perspectives. (18th January 2018) - Small, Catherine; Pistrang, Nancy; Huddy, Vyv; Williams, Claire
Abstract : Objectives: The acute inpatient setting poses potential challenges to delivering one‐to‐one psychological therapy; however, there is little research on the experiences of both receiving and delivering therapies in this environment. This qualitative study aimed to explore service users' and psychologists' experiences of undertaking individual therapy in acute inpatient units. It focused on the relationship between service users and psychologists, what service users found helpful or unhelpful, and how psychologists attempted to overcome any challenges in delivering therapy. Design: The study used a qualitative, interview‐based design. Methods: Eight service users and the six psychologists they worked with were recruited from four acute inpatient wards. They participated in individual semi‐structured interviews eliciting their perspectives on the therapy. Service users' and psychologists' transcripts were analysed together using Braun and Clarke's (2006, Qualitative Research in Psychology, 3, 77) method of thematic analysis. Results: The accounts highlighted the importance of forming a 'human' relationship – particularly within the context of the inpatient environment – as a basis for therapeutic work. Psychological therapy provided valued opportunities for meaning‐making. To overcome the challenges of acute mental health crisis and environmental constraints, psychologists needed to work flexibly and creatively; the therapeutic work also extended to the wider context of the inpatient unit, in efforts to promote a shared understanding of service users' difficulties. Conclusions: Therapeutic relationships between service users and clinicians need to be promoted more broadly within acute inpatient care. Psychological formulation can help both service users and ward staff in understanding crisis and working collaboratively. Practice‐based evidence is needed to demonstrate the effectiveness of adapted psychological therapy models. Practitioner Points: Developing 'human' relationships at all levels of acute inpatient care continues to be an important challenge for clinical practice. Due to the distress of individuals and the constraints of the acute inpatient environment, psychologists need to be flexible and adaptable in delivering individual therapy. Making meaning and psychological formulation can give service users a sense of hope and empowerment, and can contribute to a shared understanding within the ward team of service users' difficulties.